The Complexities of Being an English Lecture of Non-English Program: A Narrative Inquiry - Laksana Tri Prasetya (SALEE: Study of Applied Linguistics and English Education, 2023)
This study tells about the story as an English lecturer of non-English program at STAI Darul Ulum Kandangan. This study aims to investigate the challenges of becoming an English lecturer of non-English program in private institution and strategies in facing these challenges when the writer becomes an English lecturer. The study uses qualitative research in the form of autobiography narrative inquiry. This study shows that there are many challenges being an English lecturer in a private institution that are the challenges before entering to the classroom such as making preparation of a lesson plan for one semester, material and media, in the classroom such as facing the various students, and outside of the classroom such as doing research and dedicating him/herself for the society and the strategies that the writer used in solving these challenges. I hope that this study will be a good consideration for the next lecturer in the future.